(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The present study was conducted to find out the prevalence of Strongyloidesstercoralisin three slum areas of Dhaka, Bangladesh. Overall prevalence of S. stercoralis incollected samples was found to be 14.68%. Other enteric parasites detected in the stoolwere Ascarislumbricoides (16.08%), Trichuristrichura (8.39%) and Enterobiusvermicularis (5.59%). Male respondents showed higher prevalence (16.66%) of S.stercoralis infection compared to female (11.32%). Age group of 41-50 years showed thehighest prevalence (44.44%) compared to other age groups. Highest infestation rate wasobserved in labors (22.22%). Mud floor house dweller showed higher prevalence ofinfestation (18.66%) compared to those in cement floor. Prevalence of S. stercoralis washighest (20.77%) in community latrine users. Supplied drinking water users also showedthe higher infection rate (15.84%). Bare footed respondents showed infection rate ofabout 16.66%, whereas 11.86% was noted in those who use shoes. Asiat. Soc. Bangladesh, Sci. 41(1): 45-50, June 2015